ANALISIS DETERMINAN EFEKTIVITAS AUDITOR INTERNAL PADA INSPEKTORAT PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Sari, Dea Nurfika; Haryanto, Haryanto (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2016)
The aims of this study is to examine factors that affect (determinants) internal audit effectiveness in the public sector, Inspectorate office at Province Special Region of Yogyakarta. This study is a replication of the research that has been done by Alzeban and Gwilliam in Saudi Arabia. There are 4 (four) independent variables that affect internal audit effectiveness as dependent variable. There are competence of internal auditor, the relationship between internal and external auditor, auditee support to internal audit activity, and independence of internal auditor. The population in this research is 51 internal auditor working in Inspectorate office at Province Special Region of Yogyakarta. This study uses primary data in the form of questionnaire. All of questionnaire can be processed. The datawere collected were processed using PLS analysis with SmartPLS 3 program. Statistical tests showed that three of four independent variables, there are the competence of the internal auditor, the auditee support and the independence of the internal auditor affect the effectiveness of the internal audit. while relationship between the internal auditor with the external auditor does not affect the internal audit effectiveness Keywords: Internal auditor effectiveness, competence of internal auditor, relationship between internal and external auditor, auditee support to internal audit activity, independence of internal auditor.